2014
DOI: 10.2188/jea.je20130110
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Prevalence of Hallux Valgus in Female University Students: A Cross-Sectional Study

Abstract: BackgroundWe investigated the prevalence of hallux valgus (HV) and examined its association with various factors in a cross-sectional study of Japanese female university students.MethodsA questionnaire survey of foot symptoms, lifestyle, and body mass index (BMI) was administered to 343 women who provided informed consent at a women’s university. Footprints were obtained and bone density was measured. Associations of HV with various factors were analyzed by logistic regression analysis.ResultsBig toe pain was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
(80 reference statements)
2
31
0
Order By: Relevance
“…Our result also showed that the prevalence of HAV increases with increasing age. This is similar to the findings of Dare et al (2005) and Okuda et al (2014). In decreasing order of magnitude, the total number of subjects who had HAV in our study was: both feet 57(5.5%), left foot 49(4.7%) and right foot 27(2.6%).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our result also showed that the prevalence of HAV increases with increasing age. This is similar to the findings of Dare et al (2005) and Okuda et al (2014). In decreasing order of magnitude, the total number of subjects who had HAV in our study was: both feet 57(5.5%), left foot 49(4.7%) and right foot 27(2.6%).…”
Section: Discussionsupporting
confidence: 92%
“…It is characterized by lateral deviation of the proximal phalanx of the hallux, medial deviation of the first metatarsal bone, and subluxation of the first metartasophalangeal (MTP) joint (Dare et al, 2005). Hallux Abducto Valgus is associated with a medial prominence (bunion) at the first MTP joint which is caused by protruding head of first metatarsal bone (Janssen et al, 2014) with swollen and inflamed skin as a result of friction from shoes (Okuda et al, 2014). Bunions may also be caused by some other factors which include osteoarthritis, bursal inflammation, ganglion formation or gouty arthropathy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations